2021
DOI: 10.3389/fncel.2021.671506
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Choline Protects Against Cognitive Decline After Surgery in Mice

Abstract: Perioperative neurocognitive disorders (PNDs) are a common complication following procedures such as orthopedic surgery. Using a mouse model of tibial fracture and repair surgery, we have previously shown an increase in neuroinflammation and hippocampal-dependent cognitive deficits. These changes were ameliorated with the addition of a cholinergic agonist. Here, we sought to examine the effects of a high-choline diet for 3 weeks prior to tibial fracture surgery. We evaluated memory using novel object recogniti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 77 publications
0
2
0
Order By: Relevance
“…The expression of DCX, a marker for immature neurons, can reflect the number of immature neurons [30]. Importantly, these neurons are under non-pathological conditions and can mature into "fully-grown" neurons [49]. Recent studies have shown that surgery could significantly reduce the number of neural stem cells and immature neurons, which is associated with PND [50][51][52].…”
Section: Discussionmentioning
confidence: 99%
“…The expression of DCX, a marker for immature neurons, can reflect the number of immature neurons [30]. Importantly, these neurons are under non-pathological conditions and can mature into "fully-grown" neurons [49]. Recent studies have shown that surgery could significantly reduce the number of neural stem cells and immature neurons, which is associated with PND [50][51][52].…”
Section: Discussionmentioning
confidence: 99%
“…At confirmation of pregnancy, dams were assigned to one of two diet conditions ad libitum : a synthetic control chow (1.1 g/kg choline chloride in formula AIN-76A with choline chloride substituted for choline bitartrate, DYET #110098, Dyets, Inc., Bethlehem, PA, USA), or the same diet with 4.95 g/kg choline chloride (DYET #110210; based on previous findings from Alldred et al, 2021; Maurer et al, 2021; Meck et al, 1988; Meck & Williams, 1997; Mohler et al, 2001; Powers et al, 2021; Velazquez et al, 2013; 2020).…”
Section: Methodsmentioning
confidence: 99%